Urgent radio-medical service on board ship as an indicator of medical training of marine officers - Belobrov, Ye.P.; Torsky, V.G. (Актуальні проблеми транспортної медицини, 2011)
144 radio-medical consultations given in 2009-2010 to the officers responsible for medical aid on board ship are analyzed. All the officers have been trained according to the requirements of STCW-78/95. The Centre for urgent medical-and-sanitary reaction for search and rescue (SAR, Ukraine) has registered 30 appeals for medical aid from a passenger liner, three ocean tugs and 26 merchant ships. Among them there were appeals from 13 bulkers (39,9%), 5 universal ships (16,5%), 4 tankers (13,3%), 4 container-carries (13,3%). Medical aid was rendered by the masters in 22 (73,3%) cases, by the chief officer in 5 (17,0%) of cases and in 3 cases (9,7%) it was rendered by the second officer. Among those who needed medical aid there were 13(42,3%) citizens of Ukraine, 8 (27,3%) Filipinas, 4 (13,4%) citizens of Tanzania and Indonesia. The rest were representatives of Greece, Turkey, Cuba. Surgical problems had 8 seafarers (appendicitis – 2, abscesses-2, severe trauma with the fractures of the chest-2, fractures of the limbs – 2); nervous and psychotic episodes were on the second place (5 episodes), then cardio-vascular diseases and cutaneous diseases (4 cases), correspondingly. Infectious diseases have been diagnosed in 3 cases. The most severe case was presented by the acute poisoning with phosphine. The case was complicated with acute renal insufficiency. Another severe case was connected with a vast tumor of submaxillary area, complicated with life-threatening asphyxia. A complete recurrence on board ship there were in 32,7% cases, in 50,3% of cases the sufferers needed hospitalization to the coastal medical establishments, in 10,0% of cases helicopter evacuation was done. There were none fatalities. The medical skills of the officers from the named ships have been estimated as “good” in 53,2% of cases, “satisfactory” in 23,4% of cases and “poor’ and “very poor” – 23,3%. Conclusions: seafarers’ morbidity at the voyages is an index of both their state of health and quality of marine officers medical training